Applying composite fuels based on coal and finely dispersed wood in heat power engineering; Journal of Physics: Conference Series; Vol. 1128 : Thermophysics and Physical Hydrodynamics - Yankovsky S. A. Stanislav Aleksandrovich (2018, 2018)
Title screen